Dwa typy reakcji nadwrażliwości: anafilaksja oraz symetryczna, wyprzeniowa i zgięciowa osutka wywołana lekiem (SDRIFE), które wystąpiły u pacjenta po zażyciu aminopenicyliny - Rozłucka, Lesia; Gawlik, Radosław; Glück, Joanna (Alergologia Polska - Polish Journal of Allergology, 2023)
We present a rare case of a patient who experienced both immediate and delayed types of drug hypersensitivity reaction (DHR) to aminopenicillin with good tolerance of another β-lactam. A 56-year-old female patient reported allergic reactions to several antibiotics. After the co-administration of nonsteroidal anti-inflammatory drugs (NSAIDs) and amoxicillin/clavulanic acid the patient presented with anaphylactic shock. At the same time, the patient reported good amoxicillin tolerance. During hospitalization, DHR to NSAIDs was excluded by oral provocation. Due to the unclear history of β-lactam allergy, after negative skin test results, an oral provocation test with amoxicillin was performed. Four hours after the administration of the last dose, the patient developed symmetrical drug-related intertriginous and flexural exanthema (SDRIFE) with temperature increase to 38.5°C. Laboratory tests showed increased inflammatory parameters. After treatment with dexamethasone, paracetamol and bilastine, a gradual regression of skin rash and normalization of inflammatory parameters were observed. Further work-up confirmed good tolerance of cefuroxime axetil.